Fertigation for efficient water and nutrient management in high density cashew plantation - Yadukumar, N.; Rejani, R.; Prabhakar, B. (Journal of Plantation Crops, 2009)
An experiment was conducted to study the efficacy of fertigation for increasing the productivity of cashew under high density planting system (625 plants/ha). The optimal rate of fertilizer application was found as 125 g N, 31.25 g P2O5 and 31.25 g K2O/tree/ year through fertigation and 2 kg castor cake/tree through soil application (M3). The highest mean cashew nut yield of 2 t/ha/year and 1.96 t/ha/year was in treatments with 50% of recommended doses of fertilizers (RDF) through fertigation and 4 kg castor cake/ tree through soil application (M6) and the treatment with half the aforesaid dose (M3). The protein content was high in fertigation treatment with 50 % RDF and 4 kg neem cake/tree( M5) (42.6 %), followed by M6 and M3 (40.7 and 40.2 %,respectively). In soil application with drip irrigation separately, the nut yield ranged from 1.45 to 1.73 t/ha/year and protein content from 35.9 to 38.9 %, respectively. The lowest nut yield of 1.12 t/ha/year was in absolute control and the lowest protein content of 35.9 and 36.2 % were in M9 and absolute control, respectively. Fertigation increased the nut weight to 7.0 g, apple weight to 76.9 g and the shelling percentage to 30.06 compared to soil application with a nut weight of 6.8 g, apple weight of 70.8 g and a shelling percentage of 29.5 and absolute control with a nut weight of 6.7 g, apple weight of 69.4 g and a shelling percentage of 28.8, respectively. The highest net profits of Rs. 49,367/ha/year and Rs. 47,393/ha/year were also from fertigation plots M4 (RDF through fertigation) and M3. The net profit from absolute control (M13) was Rs.32,425/ha/year. In soil application treatments with drip irrigation separately (M7 to M12), the net profit ranged from Rs.32,235 to Rs.40,417/ha/year. Soil and water conservation measures with mulching conserved soil moisture and reduced the optimal irrigation requirement to 20% Cumulative Pan Evaporation (CPE). Hence, increased irrigation rates (40 and 60 % CPE) did not have any significant effect on growth of cashew plants, nut weight, shelling percentage, yield etc. The levels of minor and micronutrients of the soil and defatted cashew kernel flour in fertigation treatments were on par with soil application with separate drip irrigation and were high compared to absolute control (except Zn). Different irrigation rates did not have significant effect on kernel N, P, K, Ca and Mg content but increased irrigation (20 to 40% CPE) increased the concentration of most of the major and micro nutrients present in leaf.